An Anaysis of Students' Difficulties in Speaking Practice - GRAHMAYANURI, NOVRIA; KHAWARDI, LUCY; LINDA EFRINA; BATUBARA, EFIRA ANDIYANI; SRI WAHYUNI; MUHAMMAD YAMIN (ETERNAL (English, Teaching, Learning and Research Journal), 2025)
This study explores the difficulties faced by second-semester Islamic Education (PAI) students at STAI Al-Hikmah Medan in practicing English speaking. Employing a qualitative descriptive approach, data were collected through semi-structured interviews with five students. The analysis revealed five major themes: (1) limited vocabulary and grammar mastery, (2) speaking anxiety and fear of making mistakes, (3) lack of speaking practice opportunities, (4) peer pressure and unsupportive classroom environments, and (5) absence of contextual and real-life speaking applications. Students expressed challenges not only in linguistic competence but also in psychological readiness and cultural relevance of the speaking materials. This research contributes a new perspective by focusing on students in a religious academic context, highlighting the importance of integrating culturally relevant content and fostering supportive learning environments. Recommendations include increasing the frequency of speaking practice, incorporating Islamic-themed speaking materials, and creating psychologically safe spaces for language learners.